Toxicity Test of the Combination of N-Hexane Extract of Black Pepper (Piper nigrum L.) and Yogurt on the Digestive Organs of Mice (Mus musculus) - Inayah, Nurul; Mutiati, Enni; Sa’diyah, Halimatus (SAINTIS Publishing, 2024)
Black pepper (Piper nigrum L) is a spice that is widely used in cooking by people in Indonesia, earning the nickname